Recommendations for long-term follow-up care of secondary health conditions in spinal cord injury/disorder: a systematic review - Eriks-Hoogland, Inge; Jordan, Xavier; Baumberger, Michael; Seijas, Vanessa; Huber, Burkhart; Michel, Franz; Thietje, Roland; Müller, Lorena (Frontiers in Rehabilitation Sciences, 2024)
ObjectivesThe purpose of this systematic review is to provide an overview of published follow-up care programs of primary and secondary health conditions (SHCs) in spinal cord injury/disorder (SCI/D) and spina bifida and describe recommendations on content, frequency, setting of follow-up care programs for persons with SCI/D and spina bifida.MethodsAccording to the sequence of procedures of the AWMF (Association of the Scientific Medical Societies in Germany) a systematic literature search was performed (in PubMed, Cochrane Library and nine additional databases for guidelines) between 5 September 2019 and 22 September 2019. Publications (Jan. 2008–Dec. 2018) and guidelines (up to 2018) published in English or German and describing an evidence-based follow-up care program for persons with SCI/D or spina bifida were included.ResultsThe systematic literature search found 1973 publications in PubMed and Cochrane Library, resulting in 19 papers for SCI/D and 6 for Spina bifida. Additionally, we included 34 guidelines developed by reputable committees or medical associations. All eligible guidelines, and publications, were rated and classified according to the guidance of AWMF. Of the retrieved publications, and guidelines, level of evidence of follow-up care programs was mostly based on informal procedures and expert opinion or formally consent based expert opinion. None of the guidelines, or publications described an evidence based comprehensive clinical practice guideline (CPG) for follow-up care for people with SCI/D or spina bifida.ConclusionBased on the comprehensive and extensive literature research conducted, regular (annual) follow-up care appointments at specialized SCI clinics are recommended. There is a notable absence of a comprehensive CPG covering all relevant health conditions for long-term follow-up in SCI/D or spina bifida. In order to provide persons with SCI/D with up-to-date and best possible medical and rehabilitative care, a CPG for follow-up care is urgently needed. In response to this gap, the German-speaking Medical Society of Paraplegia (DMGP) has commissioned its members to establish a guideline for follow-up care for individuals with SCI/D. The current review serves as an evidence-based framework for the development of this guideline.